The role of women in Micro, Small, and Medium Enterprises (MSMEs): A case study of the Petho Cracker Business in Paremono Village, Magelang Regency - Maulida Masyitoh; Endah Yusma Pratiwi; Aldri Oktanedi; Yuanita Dwi Hapsari (Priviet Social Sciences Journal, 2025)
This study aims to analyze the driving factors and strategic roles of women in Micro, Small, and Medium Enterprises (MSMEs) producing Petho crackers (Peyek Petho) in Paremono Village, Magelang Regency. Using a descriptive qualitative approach with data collection techniques, including in-depth interviews, participatory observation, and documentation studies, this study found that women's involvement is driven by four main factors: economic needs to support uncertain family income, family inheritance, and business regeneration; promising business opportunities; and skills acquired through social learning. Women play a central and integrated role in all business aspects from capital provision and production processes to marketing strategies encompassing manual, digital, and sales agent methods. The income contribution from this business is significant for fulfilling basic household needs, financing children's education, and meeting social obligations within the community. The study concludes that women's participation in MSME transcends economic activity; it is a potent form of empowerment that successfully reconfigures traditional gender roles. Through this venture, women have expanded their agency from the domestic to the public sphere, simultaneously acting as key agents in preserving the local culinary heritage and strengthening the village's economic identity.